Little to fear: largest lizard predator induces weak defense responses in ungulate prey. (18th January 2019) - Jessop, Tim S; Ariefiandy, Achmad; Purwandana, Deni; Benu, Yunias Jackson; Hyatt, Matthew; Letnic, Mike
Abstract: Nonconsumptive effects can strongly influence apex predator ecological function. These effects arise because prey often induce costly phenotypic responses to mitigate predation risk. Yet because predator–prey interactions are complex, prey defenses may vary considerably. We investigated if the Komodo dragon ( Varanus komodoensis ), a reptile apex predator, induced multiscale antipredator responses in key prey, the Rusa deer ( Cervus timorensis ) and the wild pig ( Sus scrofa ). To this end, we examined the temporal and spatial partitioning of habitats by predator and prey, determined the size of ungulate groups as a function of risk, and assessed changes in individual behavior of prey individuals exposed to predator kairomones at feeding stations. Komodo dragon, deer, and pig populations exhibited significant, but subtle differences in 3 habitat preferences that otherwise indicated high niche overlap. Komodo dragon predation risk, alongside other commonly considered predictor variables, did not affect deer or pig group size. With the exception of one individual-based vigilance-type behavior in pigs, no other antipredator behavior, including reduced food consumption, significantly varied in the presence of predator odor cue at feeding stations. Overall, our results indicated limited evidence for antipredator behavior and suggested Komodo dragons exert weak nonconsumptive effects of predation in ungulates. However, weak predatory interactions could be beneficial in island ecosystems as it could promote predator–prey coexistence that reduces extinction risk. Abstract : Apex predators hold important ecological roles through their ability to kill and induce antipredator responses in prey. Against expectation, we provide compelling evidence that the Komodo dragon, the largest lizard predator, induces only weak antipredator responses in key prey—Rusa deer and wild pig. Low and variable energy requirements of Komodo dragons could explain limited antipredator responses. Weak predation, however, probably benefits the persistence and coexistence of Komodo dragon and prey populations on small islands.